Reconsidering Reciprocal Length Patterns of the Anteromedial and Posterolateral Bundles of the Anterior Cruciate Ligament During In Vivo Gait. Issue 8 (July 2020) - Englander, Zoë A.; Wittstein, Jocelyn R.; Goode, Adam P.; Garrett, William E.; DeFrate, Louis E.
Background: Some cadaveric studies have indicated that the anterior cruciate ligament (ACL) consists of anteromedial and posterolateral bundles that display reciprocal function with regard to knee flexion. However, several in vivo imaging studies have suggested that these bundles elongate in parallel with regard to flexion. Furthermore, the most appropriate description of the functional anatomy of the ACL is still debated, with the ACL being described as consisting of 2 or 3 bundles or as a continuum of fibers. Hypothesis: As long as their origination and termination locations are defined within the ACL attachment site footprints, ACL bundles elongate in parallel with knee extension during gait. Study Design: Descriptive laboratory study. Methods: High-speed biplanar radiographs of the right knee joint were obtained during gait in 6 healthy male participants (mean ± SD: body mass index, 25.5 ± 1.2 kg/m 2 ; age, 29.2 ± 3.8 years) with no history of lower extremity injury or surgery. Three-dimensional models of the right femur, tibia, and ACL attachment sites were created from magnetic resonance images. The bone models were registered to the biplanar radiographs, thereby reproducing the in vivo positions of the knee joint. For each knee position, the distances between the centroids of the ACL attachment sites were used to represent ACL length. The lengths of 1000 virtual bundles were measured for each participant by randomly sampling locations on the attachment site surfaces and measuring the distances between each pair of locations. Spearman rho rank correlations were performed between the virtual bundle lengths and ACL length. Results: The virtual bundle lengths were highly correlated with the length of the ACL, defined as the distance between the centroids of the attachment sites (rho = 0.91 ± 0.1, across participants; P < 5 × 10 -5 ). The lengths of the bundles that originated and terminated in the anterior and medial aspects of the ACL were positively correlated (rho = 0.81 ± 0.1; P < 5 × 10 -5 ) with the lengths of the bundles that originated and terminated in the posterior and lateral aspects of the ACL. Conclusion: As long as their origination and termination points are specified within the footprint of the attachment sites, ACL bundles elongate in parallel as the knee is extended. Clinical Relevance: These data elucidate ACL functional anatomy and may help guide ACL reconstruction techniques.